A gestão de resíduos em pequenos negócios na cidade de São Sebastião: desafios e estratégias de mitigação. - MAYER, Ana Luiza Gonçalves; NOGUEIRA, José Eduardo Santos (188, 2025)
Este trabalho busca compreender as rotinas de gestão de resíduos dos pequenos comércios de São Sebastião, evidenciando seus gargalos e omissão de informações instrutivas para a realização de tal processo. Também, análises mostram que a COOPERSUSS (Cooperativa de Trabalho, Produção e Beneficiamento União de São Sebastião) é uma aliada operacional aos empreendedores locais. Com isso, observa-se que políticas e investimentos públicos auxiliam o tratamento adequado aos resíduos gerados por empreendedores locais.

The aim of this paper is to comprehend the waste management routines of small businesses in São Sebastião, highlighting their main gaps and the omission of instructive information for the proper execution of this process. The methodology included literature review and field observations. The analyses show that COOPERSUSS (Cooperative of Work, Production and Beneficiation União de São Sebastião) acts as an operational ally for local entrepreneurs. With this, it is known that public policies and investments assist in the adequate treatment of waste generated by local entrepreneurs.
Waste management in small businesses in the city of São Sebastião: challenges and mitigation strategies.
Keywords: Resíduos sólidos (gerenciamento); Sustentabilidade; Cooperativas; Logística reversa; Preservação ambiental; Gestão e Negócios